2009
DOI: 10.1017/s0043933909000397
|View full text |Cite
|
Sign up to set email alerts
|

Continuing education in the prevention and control of HPAI: a case study on Indonesia

Abstract: Highly Pathogenic Avian Influenza (HPAI) subtype H5N1 is now endemic in large parts of Indonesia and this situation has revealed, among other constraints, a lack of human resource capacity in many institutions especially in terms of understanding of, and experience in, the control of poultry diseases. Cost-efficient prevention and control of HPAI must be built on a sustainable poultry health programme that incorporates collaborative research and development activities involving the public and private sectors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
1
8
0
1
Order By: Relevance
“…Indeed, according to the results of the model, the scenario in Figure 4C allows for the best optimization of the system’s efficiency. This underlines the importance of training local stakeholders, specifically to control avian diseases at their level, and also supports the conclusions of other studies that have shown the importance of involving local stakeholders in the improvement of the efficiency of systems of surveillance and control of HPAI H5N1 [36], and animal diseases more widely [37]. …”
Section: Discussionsupporting
confidence: 83%
“…Indeed, according to the results of the model, the scenario in Figure 4C allows for the best optimization of the system’s efficiency. This underlines the importance of training local stakeholders, specifically to control avian diseases at their level, and also supports the conclusions of other studies that have shown the importance of involving local stakeholders in the improvement of the efficiency of systems of surveillance and control of HPAI H5N1 [36], and animal diseases more widely [37]. …”
Section: Discussionsupporting
confidence: 83%
“…In view of the fact that the LBMs systems' adherence to compensation mechanism for culled birds was poorly implemented in both countries, it is recommended that a carefully structured compensation system with regular options for review should be in place in African countries. It has been confirmed that compensation encourages cooperation of LBM operators and other role players and supports voluntary reportage of outbreaks (Alders et al, 2009;Hunter et al, 2014). To reduce financial losses, the LBM operators will rapidly sell sick poultry with implications for transmission of infection.…”
Section: Discussionmentioning
confidence: 85%
“…Informational instruments, such as providing practical information, could increase the internal motivation of farmers to perform specific behaviors [( 32 ), p. 118]. To increase the adoption of HPAI control measures, practical information should be suited to the local context and promote financial benefits from implementation [( 33 ), p. 530; ( 34 ), p. 11–12]. Training programs about prevention and control of HPAI, can be used by the government to increase the knowledge and awareness about HPAI and measures to control it.…”
Section: Discussionmentioning
confidence: 99%